Gender perspective on the "Work-From-Home" set-up women's voices in the Philippine Business Process Outsourcing (BPO) Industry - Cadavos, Roxen Janna A.; Canada, Daryll Janna A.; Capaning, Rachell Anne T.; Guino-o, Kesley P.; Monteclaro, Kilianne Kyle (College of Social Sciences, University of the Philippines Cebu, 2023)
Amidst the pandemic, the Business Process Outsourcing (BPO) in the Philippine industry is striving to heighten because they were able to employ 70% of their staff to work from home (WFH); however, within this economy that has been helping the country, inequalities are still present, especially in the work from home set-up. This study is anchored to Eagly's (1987) Social Role Theory which acknowledges the classical division in labor among women and men, wherein women have had to bear a disproportionate share of the load of parenting and household responsibilities. From advancing this position, the main problem of the study is to describe the narratives and experiences of women in the BPO industry as they adopt the work-from-home set-up. This research utilized a qualitative descriptive design. Through purposive sampling, 14 women BPO agents working in Cebu were approached as respondents. The data analysis was done with the utilization of a thematic analysis. The findings of this study reveals that while the work-from-home set-up provides opportunities for women particularly in their careers, gender roles in the domestic sphere continue to persist, leaving women with no choice but to favor this work arrangement wherein they can do both productive and reproductive work. This serves as a striking illustration of the gender inequality resulting from the prevailing division of labor and entrenched stereotypes in our society.